The mobilities and immobilities of rural gentrification: Staying put or moving on?. Issue 7 (6th July 2021) - Smith, Darren P.; Phillips, Martin; Culora, Andreas; Kinton, Chloe
Abstract: This paper analyses census data for England and Wales to explore the ties between processes of rural gentrification and recent internal migration. Internal migrants are defined as individuals who moved subnationally to their current address in the previous 12 months, as indicated by the replies to the 2001 and 2011 census question about usual address 1 year ago. Our analysis reveals declining rural in‐migration rates between 2001 and 2011, in parallel with other recent studies of internal migration. At the same time, uneven geographies of rural in‐migration are identified. In rural places with declining in‐migration rates, we emphasise the immobilities of settled gentrifiers that are caused by predilections to 'stay put' within prized, rural places for age‐related personal/emotional, social/support and economic reasons. This is limiting the supply pipeline of housing for latent in‐migrants and slowing flows of migration per se in saturated rural housing markets. By contrast, rural places with increasing in‐migration rates may signify new frontiers of gentrification, providing channels of entry for recent migrants that are not able to buy into exclusive high‐cost gentrified markets. Our novel argument is that despite gentrification being inherently a process of migration, when viewed in a broader temporal perspective, mature and exclusive forms of gentrification can also stifle migration and be the catalyst for immobilities.